DETERMINANTS OF CERVICAL CANCER PREVENTION BEHAVIOR WITH IVA METHOD IN WOMEN OF FERTILE AGE IN THE WORK AREA OF JETAK COMMUNITY HEALTH CENTER - Awalis Sholihah; Eko Winarti (Suluh Adiluhung Publisher (SAPub), 2025)
Cervical cancer can be recognized at the pre-cancer stage by doing early detection test in married women. One of the cervical cancer early detection methods is Visual Inspection with Acetic Acid (IVA) test. The coverage of the early detection of cervical cancer through IVA test method in 2023 was still very low. There was 1.37% from the national target of 50%. The research aims to know the determinants of cervical cancer early detection behavior by using the IVA test method in the work area of Jetak Community Health Center. The method was observational analytical research with cross-sectional study design. The population of the study was all women of fertile couple in working are Jetak Community Health Center, Montong Distric, which amounted to 5508 women. The research sample was 246 women of fertile (who were collected using accidental sampling techniques with the inclusion criteria of married women of fertile 30 – 50 years old: The result showed that there was a direct and indirect relationship from attitudes, subjective norm and behavioral control as well as intentions towards behavior, which were very significant.